Expression of toll‐like receptors 1–5 but not TLR 6–10 is elevated in livers of patients with non‐alcoholic fatty liver disease. (12th January 2014) - Kanuri, Giridhar; Ladurner, Ruth; Skibovskaya, Julia; Spruss, Astrid; Königsrainer, Alfred; Bischoff, Stephan C.; Bergheim, Ina
Abstract Background & Aims Animal models of non‐alcoholic fatty liver disease (NAFLD) suggest that an increased translocation of bacterial endotoxins, leading to an activation of toll‐like receptor‐dependent signalling cascades (TLRs) and increased formation of reactive oxygen species, may add to development of insulin resistance and induction of plasminogen activator inhibitor‐1 (PAI‐1) in the liver. If similar mechanisms are also involved in the development of NAFLD in humans remains to be determined. Methods Toll‐like receptor (1–10), myeloid differentiation primary response gene (MyD88), interferon regulatory transcription factor 3 (IRF‐3) and insulin receptor substrate 1 (IRS‐1) mRNA expression was determined in liver samples of 11 patients with NAFLD and 11 controls. Hepatic PA1‐1 and 4‐hydroxynonenal protein adducts (4‐HNE) levels were determined by immunohistochemistry. Results Hepatic TLR 1–5 mRNAs expression was significantly higher in livers of NAFLD patients than in controls, whereas expression of TLR 6–10 mRNAs did not differ between groups. Expression of MyD88 but not IRF‐3 was also significantly higher in livers of NAFLD patients than in controls. These alterations were associated with significantly higher levels of 4‐HNE and PAI‐1 protein levels in livers of NAFLD patients than in controls, whereas IRS‐1 mRNA expression was ~80% lower in livers of NAFLD patients than in controls. Conclusions Taken together, these findings add further weight to the hypothesis that alterations at the level of intestine and intestinal barrier function may be critical in the development of NAFLD in humans.